Floristic Diversity Assessment in Corbett National Park, Ramnagar, Nainital, Uttarakhand - Bhatt, Ganesh Datt; Aggarwal, Santosh Kumar (Indian Forester, 2013)
A field survey was conducted for the floral diversity assessment in Corbett National Park, Ramnagar in February, 2006 and laid twenty sample plots in sal, sal mixed and khair-sissoo forests. The highest floral diversity as per Shannon-Wiener diversity index was found in sal, followed by sal mixed and khair-sissoo forests.